PENGARUH BUKU ELEKTRONIK TERHADAP PERILAKU MEMBACA DAN PEMAHAMAN BACAAN PADA SISWA SMA - Hana Humaira Hidayah; Luthfita Pramata Aurelia; Ichsan Fauzi Rahman M (TARBIYATUL ILMU: Jurnal Kajian Pendidikan, 2024)
This study aims to determine the effect of electronic books on reading behavior and reading comprehension in senior high school students. Education has undergone a significant transformation in the era of information technology such as the emergence of electronic books. This change will certainly affect students' reading culture which includes reading behavior and reading comprehension. This research uses a qualitative approach with a case study method. The results showed that students felt the ease of access, flexibility, and interactivity in using electronic books, thus encouraging them to use electronic books to support their academic needs. The findings of this study are the influence of electronic books on reading behavior and reading comprehension in high school students in the form of increased interest and good learning outcomes. The challenges that need to be overcome in order to maximize the potential of electronic books in high school learning are to ensure that students remain actively and critically engaged in the reading process, as well as to maintain students' focus and concentration when faced with electronic books.